Analysis of Water Quality Using Physico-Chemical Parameters in District Shangla, Khyber Pakhtunkhwa, Pakistan - Sayaf, Muhammad; Ikram Ullah; Miraj Ud Din, Said; Khan, Azmat Ali; Khan, Kamran; Khan, Ijaz Ali; Mehran Ullah (Indus Journal of Bioscience Research, 2025)
Water is a universal solvent and an important component of life. Water is said to be polluted when its composition or quality changes due to direct or indirect disposal of wastes and other human activities. There are three water quality parameters; physical, chemical and biological. These parameters serve as essential indicators for assessing the safety and suitability of water for consumption, encompassing various aspects to ensure compliance with health and environmental standards. Physicochemical parameters, which include both physical and chemical play an important role in determining the fitness of water for drinking purposes. A comprehensive study was conducted in district Shangla, Khyber Pakhtunkhwa (KPK), Pakistan to evaluate the quality of drinking water in four tehsils: Puran, Chakisar, Besham, and Alpuri. The water samples were collected from three different source including tube wells, springs, and tap water. A total of twelve water quality parameters were meticulously examined, comprising three physical parameters and nine chemical parameters. The physical parameters assessed were total dissolved solids, pH, and electrical conductivity. The chemical parameters were total hardness as calcium carbonate (CaCO3), the concentration of chloride (Cl), sulphate (SO4), sodium (Na), nitrite (NO2), calcium (Ca), magnesium (Mg), and potassium (K) and total alkalinity. The results showed significant variations in four tehsils but all the values fall within the WHO and PSQCA recommended limits except magnesium (Mg). The amount of total dissolved solids (TDS) varied greatly, ranging from 80 to 412 mg/L.